Ghrelin fiber projections from the hypothalamic arcuate nucleus into the dorsal vagal complex and the regulation of glycolipid metabolism. (December 2019) - Su, Manqing; Yan, Meixing; Gong, Yanling
Abstract: Objectives: This study aimed to explore the involvement of the ghrelin pathway from the arcuate nucleus (ARC) to the dorsal vagal complex (DVC) and to determine its role in the regulation of glycolipid metabolism. Methods: The protein and mRNA expression of ghrelin and growth hormone (GH) secretagogue receptor type 1a (GHSR-1a) were measured using immunohistochemistry and the polymerase chain reaction (PCR) method, respectively. Ghrelin fiber projections arising from the ARC and projecting into the DVC were investigated using retrograde tracing, combined with fluorescence immunohistochemical staining. The effects of electrical stimulation (ES) of the ARC on ghrelin-responsive, glucose-sensitive DVC neurons, glycolipid metabolism, and liver lipid enzymes were determined using electrical physiological method, biochemical analysis, quantitative real-time PCR (qRT-PCR) and Western blot analysis. Results: GHSR-1a was expressed in the DVC neurons. Ghrelin fibers originating from the ARC projected into the DVC. ES of the ARC-activated the ghrelin-responsive glucose-excited (GE) and glucose-inhibited (GI) neurons in the DVC. ES of the ARC significantly elevated the serum triglyceride (TG), total cholesterol (TC), low-density lipoprotein cholesterol (LDL-C), and glucose levels; it reduced the serum high-density lipoprotein (HDLC) and insulin levels. Moreover, ES of the ARC increased liver acetyl-CoA carboxylase-1 (ACC-1) and decreased carnitine palmitoyltransferase-1 (CPT-1) expression, resulting in lipid accumulation in the liver. All the aforementioned effects were partially blocked by pretreatment with the ghrelin receptor antagonist [D-Lys-3]-GHRP-6 in the DVC and were reduced by vagotomy. ES of the ARC increased agouti-related protein (AgRP)/neuropeptide Y (NPY) expression in the ARC and ghrelin expression in the DVC. Conclusion: Ghrelin fiber projections arising from the ARC and projecting into the DVC play a role in the regulation of afferent glucose metabolism and glycolipid metabolism via the ghrelin receptor GHSR-1a in the DVC.